PENGINTEGRASIAN KONTEN BUDAYA LOKAL DALAM BUKU TEMATIK PEGANGAN SISWA KELAS V SEKOLAH DASAR - Arti Prihatini (Center of Language and Cultural Studies, 2015)
This study is aimed to evaluate integration of local culture contents in the thematic textbook for the fifth grade students of Elementary School is crucial to include. This study used descriptive qualitative design. This study revealed that local culture contents incurred in the textbook comprised of: (1) internal and external local culture load, (2) development of individual and society local culture domain, (3) reading texts, istructional texts, exercises and assignments, reflection views, communication texts to students parents, and (4) implementation of local culture theories that is not yet optimally described.